Upaya Mediasi Tiongkok Dalam Penyelesaian Konflik Internal Afghanistan Tahun 2016-2021 - Madjid, Dhy'vab Yusuf; W. Sagena, Uni (Interdependence Journal of International Studies, 2025)
This research examines China's mediation efforts in resolving Afghanistan's internal conflict between 2016 and 2021, emphasizing the strategic national interests driving its involvement. Employing a qualitative explanatory method, the study utilizes secondary data gathered from scholarly literature, official reports, and policy documents. The data were analyzed using Miles and Huberman's interactive model, involving data collection, reduction, display, and conclusion. The findings demonstrate that China's mediation is primarily motivated by its economic and security interests, notably its intent to safeguard investments and curb the spread of extremism into Xinjiang. Additionally, China seeks to promote regional stability to support the broader objectives of its Belt and Road Initiative. By engaging in bilateral dialogues and multilateral platforms—including collaboration with both the Afghan government and the Taliban—China has established itself as a pragmatic and influential actor in Central Asia’s peace process. This study contributes to a deeper understanding of China's foreign policy approach, regional engagement strategies, and conflict resolution diplomacy.